Bronze Age tell communities in context : an exploration into culture, society, and the study of European prehistory. - Kienlin, Tobias L., (Archaeopress Archaeology, 2020)
This is the second part of a study on Bronze Age tells and on our approaches towards an understanding of this fascinating way of life, drawing on the material remains of long-term architectural stability and references back to ancestral place.